MODEL MATEMATIKA SEDERHANA REDAMAN GETARAN PADA SAYAP PESAWAT TERBANG - Rukmono Budi Utomo (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2016)
We have known that when the plane encountered turbulence or in a hard landing, the aircraft engine will swing to dampen vibrations of the aircraft wing. Thus, based on rights, this research is investigating and constructing mathematical model of aircraft wing vibration. In this research, we described not only the creation of mathematical models, but also the analysis of the model and its interpretation.